Decision Support System Framework for Implementation of Enterprise Resource Planning (ERP) System - Khalil, M.A.T.; P.D.D., Dominic; Hassan, M.F. (2010)
A growing challenge for today's complex decision making is the successful implementation of ERP (Enterprise Resource Planning) system. Many problems that arise in ERP implementation have been discussed and tackled by researchers in recent times. An emerging threat to the successful implementation of ERP is the wicked problems. Wicked problems manifest in somewhat enormous projects or applications. These wicked problems can lead to a huge loss of organizational intellectual property and finance. In order to counter these wicked problems, a preemptive decision making strategy needs to be adopted to anticipate these problems in ERP implementation. As such, a research investigation requires to be carried out to address the complexity and multiplicity in projects which may lead it to wicked problems and ultimately turning it into a wicked project. As of today's expanding globalization, multiple stakeholders with conflicting standpoints increase; each one linked with the organization(s) is affected by the different customs, behaviours, laws and environmental concerns. Globalization also leads to the wicked problems for the organization. Methods to help decision makers deal with wicked problems are greatly needed. In pursuit of that some elastically open ended, participative, collaborative and adaptive approaches are needed to anticipate wicked problems in ERP implementation. This paper focuses on a decision support system model for implementation of ERP system. ERP often serves as a happy hunting ground for wicked problems because of its complex and multi-pronged nature. Other than that, we are reviewing some techniques and methodologies that are recommended to assist decision makers understand the unstructured and poorly defined complexity in ERP implementation. Comparative analyses of these techniques will not only assist in better understanding wicked problems, they are also being used to provide a framework for a suitable and sustainable decision support system for implementation.